Formation of the depreciation policy mechanism of enterprises in the context of strengthening the investment security of the state - V.V. (Економіка, управління та адміністрування)
The article is devoted to the study of the depreciation policy of business entities and its impact on the investment security of the state. The purpose of the article is to study the process of reproduction of non-current assets and the formation of the mechanism of depreciation policy of enterprises in the context of strengthening the investment security of the state. According to the results of the conducted econometric analysis, it was concluded that depreciation as a source of reproduction of fixed assets practically does not fulfill its function, that is, the amounts of accrued depreciation, which are returned as part of the revenue to the enterprise and subsequently form the balance sheet profit, practically do not contribute to the restoration of fixed assets, but are used for replenishment of current assets. This fact requires the government to realize the priority of depreciation as an important source of financing and stimulation of the processes of updating the material and technical base of production, which should be clearly reflected in the goals and objectives of the Strategy for the recovery of Ukraine and its economy. The expediency of moving away from the policy of liberalization of economic relations in the sphere of reproduction and the need to return state control over the targeted use of depreciation funds, which will contribute to the restoration of the destroyed economic potential of Ukraine during the military aggression of the Russian Federation, are substantiated. The need to restore the investment potential of the state not only at the expense of external investments, but also to restore the full functioning of the involvement of internal sources requires the formation of new progressive approaches to align the interests of the state and enterprises, especially in the conditions of martial law and post-war reconstruction. The article proposed the mechanism of formation and implementation of depreciation policy in modern conditions. Implementation of the proposed depreciation policy mechanism will provide an opportunity to: harmonize the interests of the state and the enterprise in the accumulation of investment resources; to form a reliable financial reserve for the restoration of fixed assets at the macro level and to ensure the indicator of gross accumulation at the macro level, which will contribute to strengthening the investment and innovation security of the state; to motivate enterprises to direct depreciation funds to update non-current assets, which will contribute to the saving of other types of own financial resources (including profit).